Lambda2 light chains in normal mouse immunoglobulins. - Blaser, K (1978)
Light (L) chains of the lambda type are rare in mouse immunoglobulins. One lambda chain, the L chain of myeloma protein 315 (L315), differs in amino acid sequence at many positions in the COOH-terminal domain from all other lambda chains whose sequences have been determined (called lambda1 chains). To determine whether chains of the L315 type (called lambda2) occur in normal mouse immunoglobulins, we synthesized the COOH-terminal peptides expected in tryptic digests of K, lambda1, and L315 and developed procedures to separate the S-carboxymethyl derivatives of these peptides. Peptide maps of tryptic digests of [14C]carboxymethyl-labeled L chains from normal serum immunoglobulins showed that about 1% of mouse 7S immunoglobulins have L chains of the L315 or lambda2 type.